The elicitation of early defence responses and improvement of disease resistance in oil palm by extracellular proteins from Ganoderma boninense - Hamid, Sathyapriya; Abdullah, Siti Nor Akmar; Ho, Chai-Ling; Wong, Mui-Yun (Springer Nature, 2025)
Ganoderma boninense, a basidiomycete that causes basal stem rot (BSR) disease, threatens oil palm production and causes significant economic losses. An eco-friendly alternative to chemical BSR management is needed. This study investigated the impact of the extracellular protein sample from G. boninense on early defence responses and disease resistance in oil palm using histochemical, biochemical, and molecular approaches. The extracellular protein sample caused hypersensitive response (HR)-associated cell death, leading to rapid necrosis, and induced reactive oxygen species (ROS) production in oil palm leaf sections at 24 h post infiltration. Cell death was confirmed by trypan blue staining, and increased superoxide anion radicals and hydrogen peroxide were detected using nitroblue tetrazolium and 3′–3′ diaminobenzidine staining, respectively. The extracellular protein sample significantly increased the activities of superoxide dismutase (SOD) and guaiacol peroxidase (GPx) in the roots. The SOD and GPx activities were greater than 100 U mg−1 FW and 16 U mg−1 protein, respectively, at 12, 24, 48, and 72 h post treatment (hpt). Additionally, respiratory burst oxidase homolog B (RbohB) expression increased 2.5-fold in treated roots at 12 hpt, indicating ROS accumulation and supporting HR induction by the extracellular protein sample. In a greenhouse trial, the application of the extracellular protein sample led to a 71.43% reduction in BSR incidence in oil palm nine months after inoculation. These findings demonstrate the potential of using extracellular protein sample from G. boninense as an effective and eco-friendly BSR management tool. © Koninklijke Nederlandse Planteziektenkundige Vereniging 2025.